Histone lactylation-derived TET2 enhanced Arg1-mediated MDSC immunosuppression - Da, Wenxin; Dai, Yao; Shen, Bo; Zhang, Yan; Bao, Pengtao; Zhu, Wei; Wang, Deqiang; Wang, Shengjun; Ma, Jie (Frontiers in Immunology, 2026)
In the tumor microenvironment (TME), tumor cells secrete a large amounts of lactate due to the “Warburg effect”, which plays a significant role in regulating gene transcription. Recently, the role of lactate in gene transcription has been increasingly understood. Myeloid-derived suppressor cells (MDSCs) are inhibitory cells of bone marrow origin that possess marked abilities to suppress immune cell responses. Within the TME, MDSCs inhibit T cell-mediated specific anti-tumor immunity, as well as non-specific anti-tumor immunity mediated by NK cells and macrophages, by expressing high levels of Arg1, iNOS, and ROS.MethodsThis study used the Lewis lung carcinoma cell line to establish a lung cancer xenograft model; MDSCs were isolated from the spleens of these mice for subsequent experiments. Protein expression was analyzed by Western blotting, mRNA expression by qRT-PCR, protein-DNA interactions by ChIP-qPCR, and DNA methylation by MSP-qPCR.ResultThis research shows that histone lactylation enhances the immunosuppressive function of MDSCs. Mechanistically, lactate-induced histone lactylation upregulates TET2, which, using STAT3 as a bridge, modulates ARG1 promoter methylation to upregulate its expression and ultimately enhance the immunosuppressive function of MDSCs.ConclusionThis research reveals that the histone lactylation-mediated alteration of TET2 presents a novel therapeutic target for cancer treatment.